Pengembangan Sistem Prioritisasi Kebutuhan Perangkat Lunak menggunakan Hierarchical Cumulative Voting (HCV) - Ahmad Faizal; Denny Sagita Rusdianto; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Functional requirements represent descriptions of services that the system must fulfill. In the requirement engineering process, the functional requirements obtained from many stakeholders have the potential to conflict, so that the selection process and prioritizing requirements of stakeholders are needed. Requirements prioritization can minimize conflicts between stakeholders because the priorities of each requirement can be accepted by all groups. Requirement prioritization can prevent occurrence of scope creeps, namely situation of widening requirements because clients continue to make additions. The Hierarchical Cumulative Voting (HCV) method is one of requirement prioritization method that is formed from a combination between Analytical Hierarchy Process (AHP) and Cumulative Voting (CV). HCV method has several advantages, including faster execution times, supporting hierarchical structures, and suitable for large-scale requirements. Through the application of HCV method, a web-based software requirements prioritization system was developed to facilitate analysts in exploring and prioritizing requirements. Requirements that have been arranged in the form of hierarchies according to the level, the voting process is carried out to get the final priority value. This system has been tested with white-box testing techniques for unit and integration testing, as well as black-box testing techniques for validation testing with valid results in each test case.